FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DALAM PERSPEKTIF TEORI AGENSI DAN TEORI STAKEHOLDER (Students' Journal of Accounting and Banking, 2015)
These study examines the effect of Corporate Social Responsibility, managerial ownership, institutional ownership, public ownership, and debt policy on firm value. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2011 to 2013. Method of analysis using multiple regression analysis. The results showed that Corporate Social Responsibility has positive effect and significant to the firm value. Whereas managerial ownership, institutional ownership, public ownership, and debt policy had no significant effect on firm value.Keywords: Corporate Social Responsibility, Managerial Ownership, Institutional Ownership, Public Ownership, Debt Policy and Firm Value